Antioxidant, Antimicrobial and Anticancer Activities of the Aspergillin PZ and Terphenyllin Secondary Metabolites: An in vitro Study - Erden, Yavuz; Tekin, Suat; Betul Ceylan, Kevser; Tekin, Cigdem; Kirbag, Sevda (Gazi Univ, 2019)
The importance of secondary metabolites obtained from fungi is increasing day by day in terms of human health. Many physiological and pharmacological effects, mainly antimicrobial, anticancer and antioxidant properties of these compounds have been reported. Aim of this study is to determine the anticancer, antioxidant and antimicrobial effects of aspergillin PZ and terphenyllin compounds, which are isolated from Aspergillus and also subjected to limited number of studies. The antimicrobial activity of aspergillin PZ and terphenyllin compounds was determined by using disc diffusion method using different bacteria. The antioxidant property of the compounds was determined by measuring the level of DPPH free radical scavenging. Cytotoxic activity was determined by experiments on human prostate cancer cell lines (PC3 and LNCaP) and over cancer cell line (A2780). Both compounds showed low antimicrobial activity on test bacteria (approximately 2-3 mm zone). High concentrations of applied compounds showed apparent DPPH free radical scavenging activity, while % scavenging activity was quite low at low concentrations. Both compounds showed significant anticancer activity on cancer cell lines (p <0.05). Our results suggest that these two compounds have important biological properties due to their antioxidant and anticancer activities.
Keywords: Aspergillin PZ; Terphenyllin; Anticancer activity; Antimicrobial activity; Antioxidant activity